Depressão e apoio social percebido por mães de crianças hospitalizadas - Leone, Amanda de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
This study was performed as a requirement of the final course in Nursing. The study is cross-cutting, in order to identify associations between socioeconomic factors, education, child hospitalization in the ICU or not, degree of depression and level of social support (material, affective, emotional, informational and positive social interaction) and how to identify subgroups of mother - child vulnerable. Constitute themselves as subjects, mothers of children 0 to 17 years, 11 months and 29 days in hospital after the second day of hospitalization in the pediatric unit of a State Hospital Interior Paulista. Data collection was initiated after obtaining the assent of the Research Ethics Committee, as well as signing the consent form. We used the following instruments to collect data: the data form for socioeconomic and hospitalization; Beck Depression Inventory and Medical Outcomes Study (MOS). We obtained the result that there is a strong association between availability and social support and income per capita and the degree of depression, but did not find an association between time and hospital stay and whether the child was admitted to the ICU or not. We conclude that it is necessary to establish treatment services from the patient’s family, plus an appropriate social service support to meet this big demand for mothers who need support

Trata-se de estudo de natureza transversal, com objetivo de Identificar associações entre fatores socioeconômicos, escolaridade, internação da criança em UTI ou não, grau de depressão e categorias de apoio social (material, afetivo, emocional, de informação e interação social positiva), bem como Identificar os subgrupos de binômio mãe - criança vulneráveis. Constituíram-se como sujeitos, mães de crianças de 0 a 17 anos, 11 meses e 29 dias, hospitalizadas a partir do segundo dia de internação, em Unidade de Pediatria de um Hospital Estadual do Interior Paulista. A coleta de dados foi iniciada após a obtenção de parecer favorável do Comitê de Ética em Pesquisa, bem como da assinatura do Termo de Consentimento Livre e Esclarecido. Foram utilizados os seguintes instrumentos de coleta de dados: formulário referente aos dados socioeconômicos e de internação; Inventário de Beck e Medical Outcomes Study (MOS). Os resultados demonstraram que há uma forte associação entre a disponibilidade e apoio social e renda per capta e o grau de depressão, porém não se encontrou associação entre tempo e internação e se a criança se encontrava internada na UTI. Recomenda-se a criação de Serviços de Apoio à família com vistas ao desenvolvimento da criança
Keywords: Crianças - Assistencia hospitalar; Família - Aspectos sociais